Statistics for UiTM - Lau, Too Kya; Phang, Yook Ngor; Zainudin Awang (Oxford Fajar Sdn. Bhd, 2019)
The content of the book are based on Basic Statictics and Business Statistics syllabuses. This book is suitable for student who are taking the diploma or degree program in business studies, business insurance, banking, marketing, public administration, accountancy, hotel managament and tourism, applied sciences, computer science, quantitative methods, statistics, actuarial science and engineering program in institutes of higher learning.